Phytochemical Profile and Biological Activities of the Endemic Thymbra nabateorum Occurring in AlUla County, NW Saudi Arabia - Mohamed Djamel Miara; Sami Youssef; Yassine Fendane; Hassan Boukcim; Sami D. Almalki; Shauna K. Rees; Benjamin P. Y.-H. Lee; Abdalsamad Aldabaa; Hamdi Bendif; Ahmed H. Mohamed (Molecules)
Thymbra nabateorum, a plant species from the Lamiaceae family, is endemic to the Nabatian region, which spans southern Jordan and northwestern Saudi Arabia. It is renowned for its traditional uses and rich phytochemical profile. This study aims to examine the phytochemical composition of T. nabateorum and evaluate its biological activities, including antioxidant capacity, cytotoxic effects on cancer cell lines, and enzyme inhibition relevant to diabetes and neurodegenerative diseases. The essential oil (EO) and methanol extract of T. nabateorum were analyzed using Gas Chromatography–Mass Spectrometry (GC-MS) and High-Performance Liquid Chromatography (HPLC). Antioxidant activity was assessed using the DPPH radical scavenging assay. Cytotoxicity was evaluated against MDA-MB231 and LNCaP cancer cell lines using the MTT assay. Enzyme inhibition assays were conducted to determine the inhibitory effects on α-amylase, α-glucosidase, and butyrylcholinesterase. GC-MS analysis revealed thymol (82.30%) as the major component of the essential oil, while HPLC identified significant phenolic compounds in the methanol extract, including diosmin (118.75 mg/g) and hesperidin (22.18 mg/g). The DPPH assay demonstrated strong antioxidant activity, with the methanol extract showing an IC50 of 11.97 μg/mL for α-amylase and 31.99 μg/mL for α-glucosidase, indicating notable antidiabetic potential. Cytotoxicity tests revealed significant antiproliferative effects against both cancer cell lines, with lower IC50 values compared to standard treatments. T. nabateorum exhibits substantial antioxidant, cytotoxic, and enzyme inhibition activities, supporting its traditional medicinal uses. These findings provide a scientific basis for further research into its bioactive compounds and potential applications in modern pharmacology, particularly in developing natural therapeutic agents for oxidative stress-related diseases and cancer.